Livestock Sector Climate Finance Flows in Ethiopia, Kenya, Tanzania and Uganda - Rugerri, Michael (International Livestock Research Institute, 2024)
The objective of this analysis was to map climate finance flows for the livestock sector and related systems in East Africa in general and, more specifically, Ethiopia, Kenya, Uganda and Tanzania, given the importance of the sector in their respective economic systems and its identification as a priority in the national climate adaptation and mitigation discourse.